Unravelling the rate of action of hits in the Leishmania donovani box using standard drugs amphotericin B and miltefosine. - Diana Tegazzini; Juan Cantizani; Imanol Peña; Julio Martín; Jose M Coterón (Public Library of Science (PLoS), 2017)
In recent years, the neglected diseases drug discovery community has elected phenotypic screening as the key approach for the identification of novel hit compounds. However, when this approach is applied, important questions related to the mode of action for these compounds remain unanswered. One of such questions is related to the rate of action, a useful piece of information when facing the challenge of prioritising the most promising hit compounds. In the present work, compounds of the "Leishmania donovani box" were evaluated using a rate of action assay adapted from a replicative intracellular high content assay recently developed. The potency of each compound was determined every 24 hours up to 96 hours, and standard drugs amphotericin B and miltefosine were used as references to group these compounds according to their rate of action. Independently of this biological assessment, compounds were also clustered according to their minimal chemical scaffold. Comparison of the results showed a complete correlation between the chemical scaffold and the biological group for the vast majority of compounds, demonstrating how the assay was able to bring information on the rate of action for each chemical series, a property directly linked to the mode of action. Overall, the assay here described permitted us to evaluate the rate of action of the "Leishmania donovani box" using two of the currently available drugs as references and, also, to propose a number of fast-acting chemical scaffolds present in the box as starting points for future drug discovery projects to the wider scientific community. The results here presented validate the use of this assay for the determination of the rate of action early in the discovery process, to assist in the prioritisation of hit compounds.